Keragaman Kelelawar Insektivora Sub-Ordo Microchiptera di Stasiun Penelitian Way Canguk. Taman Nasional Bukit Barisan Selatan: Insectovorus btas diversity of Microchireptera Sub Order in Way Canguk Reserach Station, Bukit Barisan Selatan National Park - Agus P. Kartono; Karlina F. Kartika; Ibnu Maryanto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2009)
Insectivorus bat have an important ecological role as biological control for nocturnal insect population. Oneindividual insectivorus bat eats up to 600 individuals' number of insect in an hour. Insectovorus bat from Microchiroptera sub order, dependent on intact expanses for forest. Nowdays, forest as a bat habitat has severe loss caused by logging, forest conversion, and fire, which in turn lead to a decrease habitat quality and quantity. Diversity of Microchiroptera was investigated in an intact forest and secondary forset which burnt in 1997, in Way Canguk Research Station at Bukit Barisan Selatan National Park from June to December 2007. The total sampling effort using harp trap were95 traps night, investigating on each habitat using four harp traps. This study captured 1723 individuals of 19 species and five families consisct of 1382 individuals of 19 species in intact primary forest and 341 individulas of 15 species in seconderay forest. Bat family was caught in this study are Hipposideridae, Vespertilionidae, Rhinolophidae, Megadermatidae, and Nyteridae. Shannon's diversity index in secondary forest is 2.0527±0.0026 higher than primary forest (1.5424±0.0012). The K. intermedia, M. cyclotis, R. trifoliatus, and H. diadema species are only found in primary forest. H. larvatus is the insectivorus bat species most abundance in Way-Canguk Station Research.